Growth arrest-specific gene 6 (GAS6) - Fernández-Fernández, Laura; Bellido-Martín, Lola; García de Frutos, Pablo (Thrombosis and Haemostasis, 2008)
GAS6 (growth arrest-specific 6) belongs structurally to the family of plasma vitamin K-dependent proteins. GAS6 has a high structural homology with the natural anticoagulant protein S, sharing the same modular composition and having 40% sequence identity. Despite this, the low concentration of GAS6 in plasma and the pattern of tissue expression of GAS6 suggest a distinct function among vitamin-K dependent proteins. Indeed, GAS6 has growth factor-like properties through its interaction with receptor tyrosine kinases of the TAM family; Tyro3, Axl and MerTK. GAS6 employs a unique mechanism of action, interacting through its vitamin K-dependent GLA (γ-carboxyglutamic acid) module with phosphatidylserine-containing membranes and through its carboxy-terminal LamG domains with the TAM membrane receptors. During the last years there has been a considerable expansion of our knowledge of the biology of TAM receptors that has lead to a clear picture of their importance in inflammation, haemostasis and cancer, making this system an interesting target in biomedicine. The innate immune response and the coagulation cascade have been shown to be interconnected. Mediators of inflammation are essential in the initiation and propagation of the coagulation cascade, while natural anticoagulants have important anti-inflammatory functions. GAS6 represents a new player in this context, while protein S seems to have new functions beyond its anticoagulant role through its interaction with TAM receptors.
Keywords: Vitamin K; growth factors; innate immunity; inflammation; receptor tyrosine kinases; GLA